Synthesis and spectroscopic characterizations of Cu(II) complexes with novel 15‐membered N4 macrocyclic ligand and their utility to obtain CuO nanostructures for efficient degradation of dyes. (21st July 2017) - Adam, Abdel Majid A.; Alhadhrami, A.; Saad, Hosam A.; Refat, Moamen S.
Abstract : This paper describes synthesis, characterization and application of a series of Cu(II) complexes with a novel 3‐thioxo‐[1, 2, 4, 5]tetrazocane‐6, 8‐dione (N4 ) macrocyclic ligand. The complexes were characterized by physicochemical and spectroscopic techniques, such as UV–visible and IR spectroscopies, molar conductance, magnetic susceptibility measurements, and elemental analysis. The data suggest that the mononuclear Cu(II) complexes have a metal‐to‐ligand mole ratio of 1:1 and that the Cu(II) ions are coordinated with the four nitrogen atoms inside the N4 macrocyclic ring. The experimental anisotropic g ‐values indicate that the chloro, nitrato, acetate, and perchlorato complexes have six‐coordinate distorted octahedral behavior, whereas the sulfato complex has five‐coordinate square‐pyramidal geometry. A simple and nontoxic method for preparation of CuO nanoparticles based upon the thermal decomposition of the synthesized Cu(II) complexes has been explored. Finally, the degradation of Rhodamine 6G dye by the catalytic performance of nano‐sized CuO material has been evaluated. Abstract : A novel 15‐membered N4 macrocyclic ligand was prepared. The direct thermal decomposition of the nitrato Cu(II) complex with this ligand leads to a CuO material with an unusual ice shovel‐like‐shaped morphology involving a highly organized nanoscale structure.